Screens, Apps, and Digital Books for Young Children: The Promise of Multimedia - Adriana G. Bus; Susan B. Neuman; Kathleen Roskos (SAGE Publishing, 2020)
Just beginning to understand the potentials new technologies might bring to the learning environments of young children, we invited authors to submit articles that investigate multimedia sources and their effect on learning settings. Two main themes emerged-how digitization changes the learning environment and adult-child interaction in particular and which digital affordances enrich digital materials and how these changes affect learning. We finish with "alerts" to further explore more the hidden potentials of new technologies and how routines such as book reading might change and become more effective in some respects.